Quarter Life Crisis Pada Masa Emerging Adulthood - Firman Bayu Permana; Augustina Sulastri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
During their lifetime, humans will face a complicated period of development starting from children, adolescents, adults, to the elderly period. The period from adolescence to adulthood will face challenges that impact individuals, which are identified as quarter life crisis. Quarter life crisis is a response to individual unpreparedness for increasing uncertainty, incompetence, continuous change, too many choices, and feelings of panic that appear in individuals with an age range of 18 years to 29 years. The purpose of this study is to provide an overview of the quarter life crisis in emerging adulthood. The method used is library research consisting of 10 research journals conducted by searching for literature reviews, reading relevant research reports, and analyzing them in depth to obtain empirical findings from previous research. The results of this study are that there are seven dimensions of quarter life crisis, namely doubts in decision making, feelings of hopelessness, judging themselves negatively, feeling entangled in difficult conditions, anxiety, feeling depressed, and concerns with interpersonal relationships. Variables associated with quarter life crisis are emotional intelligence, peer social support, age, perceived level of happiness, perceived level of distress, intolerance of uncertainty, self-esteem, Consideration of Future Consequences (CFC), Coping Self Efficacy (CSE), gender, self-concept, well-functioning family, and self-efficacy. Quarter life crisis has an impact on the social, mental health, emotional aspects of individuals and can be prevented by active efforts of individuals to get out of difficult times to find life goals. It is hoped that from this review, individuals in the emerging adulthood development phase can understand about quarter life crisis, know the influencing factors and can anticipate the impact that occurs during quarter life crisis. Selama masa hidupnya, manusia akan menghadapi masa perkembangan yang rumit dimulai dari anak-anak, remaja, dewasa, hingga pada periode usia lanjut. Masa remaja menuju dewasa akan menghadapi tantangan yang berdampak pada individu, yang diidentifikasi sebagai quarter life crisis. Quarter life crisis adalah respon mengenai tidak siapnya individu atas ketidakpastian yang meningkat, ketidakmampuan, perubahan yang berkelanjutan, pilihan yang terlalu banyak, dan perasaan panik yang tampak pada individu dengan rentang usia 18 tahun hingga 29 tahun. Tujuan dari penelitian ini adalah untuk memberikan gambaran mengenai quarter life crisis pada masa emerging adulthood. Metode yang digunakan adalah penelitian pustaka berjumlah 10 jurnal penelitian dilakukan dengan mencari kajian literatur, membaca laporan penelitian yang relevan, dan menganalisis secara mendalam agar memperoleh temuan empiris dari penelitian sebelumnya. Hasil dari penelitian ini adalah ada tujuh dimensi quarter life crisis, yaitu keraguan dalam pengambilan keputusan, perasaan putus asa, menilai dirinya secara negatif, perasaan terjerat dalam kondisi sulit, timbul kecemasan, perasaan tertekan, dan kekhawatiran dengan relasi interpersonal. Variabel yang terkait dengan quarter life crisis yakni kecerdasan emosional, dukungan sosial teman sebaya, usia, tingkat kebahagiaan yang dirasakan, tingkat kesulitan yang dirasakan, intoleransi terhadap ketidakpastian, self-esteem, Consideration of Future Consequences (CFC), Coping Self Efficacy (CSE), jenis kelamin, konsep diri, keluarga yang berfungsi baik, dan efikasi diri. Quarter life crisis berdampak pada aspek sosial, kesehatan mental, emosional individu dan dapat dicegah dengan upaya aktif individu agar dapat keluar dari masa sulit hingga menemukan tujuan hidup. Diharapkan dari tinjauan ini, individu pada fase perkembangan emerging adulthood dapat memahami mengenai quarter life crisis, mengetahui faktor yang mempengaruhi dan dapat mengantisipasi dari dampak yang terjadi selama masa quarter life crisis.